Geodynamic evolution of a forearc rift in the southernmost Mariana Arc. (21st October 2013) - Ribeiro, Julia M.; Stern, Robert J.; Martinez, Fernando; Ishizuka, Osamu; Merle, Susan G.; Kelley, Katherine; Anthony, Elizabeth Y.; Ren, Minghua; Ohara, Yasuhiko; Reagan, Mark; Girard, Guillaume; Bloomer, Sherman
Abstract: The southernmost Mariana forearc stretched to accommodate opening of the Mariana Trough backarc basin in late Neogene time, erupting basalts at 3.7–2.7 Ma that are now exposed in the Southeast Mariana Forearc Rift (SEMFR). Today, SEMFR is a broad zone of extension that formed on hydrated, forearc lithosphere and overlies the shallow subducting slab (slab depth ≤ 30–50 km). It comprises NW–SE trending subparallel deeps, 3–16 km wide, that can be traced ≥ ∼30 km from the trench almost to the backarc spreading center, the Malaguana‐Gadao Ridge (MGR). While forearcs are usually underlain by serpentinized harzburgites too cold to melt, SEMFR crust is mostly composed of Pliocene, low‐K basaltic to basaltic andesite lavas that are compositionally similar to arc lavas and backarc basin (BAB) lavas, and thus defines a forearc region that recently witnessed abundant igneous activity in the form of seafloor spreading. SEMFR igneous rocks have low Na8, Ti8, and Fe8, consistent with extensive melting, at ∼23 ± 6.6 km depth and 1239 ± 40°C, by adiabatic decompression of depleted asthenospheric mantle metasomatized by slab‐derived fluids. Stretching of pre‐existing forearc lithosphere allowed BAB‐like mantle to flow along the SEMFR and melt, forming new oceanic crust. Melts interacted with pre‐existing forearc lithosphere during ascent. The SEMFR is no longer magmatically active and post‐magmatic tectonic activity dominates the rift.